Analysis of Farmer's Readliness to Adopt Smart Farming Technology in Smallholder Coffee Plantations in Central Aceh Regency - Ferdian Triady (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2026)
This study aims to analyse the readiness level of smallholder coffee farmers in Central Aceh District to adopt smart farming technology, particularly the use of fertiliser sensors. The research employs both quantitative and qualitative approaches through Structural Equation Modelling (SEM) using SmartPLS 4.0. Data were collected from 100 farmers in four purposively selected sub-districts using proportional sampling. The results reveal that farmers’ readiness is at a moderate level, with average scores for knowledge, motivation, and resource availability at 3.4. Farmer characteristics and access to information and infrastructure have a positive and significant influence on adoption readiness. The findings also highlight the mediating role of farmers’ perceptions. The study underscores the need for institutional support and digital literacy enhancement to foster a technology-based agricultural transformation in rural areas.